2022
DOI: 10.1186/s40902-022-00345-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical investigation of patients with jaw deformity with comorbidities

Abstract: Background With improvements in the safety and stability of surgeries, the number of orthognathic surgeries is increasing. Most patients who undergo orthognathic surgeries are younger, and the number of orthognathic surgeries for patients with comorbidities is also increasing. We report a survey and clinical investigation of patients with comorbidities who underwent orthognathic surgeries at our department to improve the safety of orthognathic surgery. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In contrast, a recent study showed that although tranexamic acid effectively controlled intraoperative blood loss and improved the quality of the surgical site, it did not exhibit any effect on postoperative levels of hemoglobin or hematocrit or the need for blood transfusion [ 20 ]. Appropriate management of patients with bleeding disorders includes the presurgical development of management strategies aimed at minimizing bleeding by shortening the surgical duration and using local hemostatic agents [ 7 , 16 ]. In the current study, intravenous or topical administration of tranexamic acid was carried out postsurgically in all patients, and local hemostatic agents were used during surgery to control bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a recent study showed that although tranexamic acid effectively controlled intraoperative blood loss and improved the quality of the surgical site, it did not exhibit any effect on postoperative levels of hemoglobin or hematocrit or the need for blood transfusion [ 20 ]. Appropriate management of patients with bleeding disorders includes the presurgical development of management strategies aimed at minimizing bleeding by shortening the surgical duration and using local hemostatic agents [ 7 , 16 ]. In the current study, intravenous or topical administration of tranexamic acid was carried out postsurgically in all patients, and local hemostatic agents were used during surgery to control bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical interventions present a critical hemostatic challenge in patients with VWD, necessitating careful perioperative management to minimize the risk of bleeding. Although previous studies have reported minor oral surgical treatment or dental extraction in patients with VWD, there is limited evidence of orthognathic surgeries in this population [ 4 , 7 ]. The current case report focuses on four patients with VWD (including one with type 3 VWD) who were successfully treated using orthognathic surgical intervention.…”
Section: Introductionmentioning
confidence: 99%